CNC Plotter: An Educational Prototype for Intelligent Automation - Paudel, Kripesh; Gurung, Suresh; Luitel, Urusha; Gaurav , Gaurav; Nakarmi, Smriti (KEC Journal of Science and Engineering, 2026)
This paper illustrates the development of a CNC plotter as an educational prototype for intelligent automation. The system illustrates how computer vision, G-code execution, and AI-based decision making can all be integrated together into a CNC platform. The system has two modes: a drawing mode, where you can create text and pictures, and a gaming mode, where the plotter plays tic-tac-toe against a person. The hardware setup relies on an Arduino Uno, NEMA 17 stepper motors, and an SG90 servo motor, while the software setup includes Inkscape, Universal G-code Sender, and GRBL firmware. A custom-trained YOLOv11 model detects board states, while the Minimax algorithm with Alpha-Beta pruning calculates the most optimal moves. The experimental results show that user designs are accurately reproduced, gameplay performance is reliable, and symbols are classified nearly perfectly. The potential of integrating CNC technology and machine learning for the purpose of education and prototyping in intelligent automation is showcased in the project.